Current Status and Major Challenges to the Safety and Efficacy Presented by Chinese Herbal Medicine - Xian Zhou (Medicines, 2019)
Traditional Chinese medicine (TCM) is not only used prevalently in Asian countries but has also gained a stable market globally. As a principal form of TCM, Chinese herbal medicine (CHM) is comprised of treatments using multiple Chinese herbs which have complex chemical profiles. Due to a lack of understanding of its modality and a lack of standardization, there are significant challenges associated with regulating CHM’s safety for practice and understanding its mechanisms of efficacy. Currently, there are many issues that need to be overcome in regard to the safety and efficacy of CHM for the further development of evidence-based practices. There is a need to better understand the mechanisms behind the efficacy of CHM, and develop proper quality standards and regulations to ensure a similar safety standard as Western drugs. This paper outlines the status of CHM in terms of its safety and efficacy and attempts to provide approaches to address these issues.